PERBANDINGAN METODE FUZZY TIME SERIES CHEN DAN METODE EXPONENTIAL SMOOTHING DALAM MEMPREDIKSI CURAH HUJAN DI KABUPATEN PAMEKASAN - Tamam, Moh. Badrit; Kuzairi, Kuzairi; Yulianto, Toni; Faisol, Faisol; Yudistira, Ira; Amalia, Rica (Jurusan Teknik Informatika Fakultas Teknik Universitas Trunojoyo Madura, 2024)
This research aims to predict rainfall in Pamekasan Regency, Madura, East Java, using two prediction methods: Fuzzy Time Series Chen and the Exponential Smoothing (ES) method, specifically Double Exponential Smoothing (DES). The data used in this study consists of monthly rainfall data from January 2011 to December 2023, covering a period of 13 years. The data was sourced from reliable records that regularly track rainfall in the region. In the analysis, both methods were applied to generate accurate predictions of rainfall patterns in Pamekasan Regency. Based on the calculations and performance evaluation, the best method for predicting rainfall in this region was found to be Double Exponential Smoothing Holt. This method uses two key parameters: alpha at 0.4 and beta at 0.6. After applying this method, a Mean Absolute Percentage Error (MAPE) of 1.479 was obtained, indicating a very low and acceptable level of prediction error. Therefore, it can be concluded that the Double Exponential Smoothing Holt method is an effective and accurate approach for predicting rainfall in Pamekasan Regency based on the historical data used..Keywords: Rainfall; Pamekasan Regency; Prediction; Chen's Fuzzy Time Series and Exponential Smoothing (ES) Method